Socialization of Making Silage for Animal Feed to the Community in Empas Village, Melak District, West Kutai Regency - Veronika; Ningsih, Riyan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2025)
Empas Village is located in Selaka District, West Kutai Regency and has many village people who choose to raise their livestock as their side jobs. However, people who raise livestock in Empas Village face a problem, namely there is no availability of feed caused by the green rainy season will be abundant but if they have entered the dry season, it will decrease other than that it is also caused by uncertain climate conditions. Therefore, activities of community service are carried out by conducting socialization to provide education about fermented green education using EM4 (silasses) as livestock feed. This activity was carried out to help the Empas village people who have livestock such as cows and are carried out by devotion methods, training to farmers. Based on the results from making livestock feed carried out using EM4 proved to give good organoleptic results